(untitled) (REMUNOM, 2023)
There are more than 2,000 clinical trial registrations worldwide to investigate approved medicines and other candidates for Covid-19, including small molecules and biological medicines, excluding vaccines. Drug repositioning, the most explored strategy to date, has not led to any new antiviral treatment against Covid-19. Remdesivir, despite its emergency approval by the North American regulatory agency, has shown only modest results in clinical studies. Dexamethasone, which contributed to reducing mortality in critically ill patients receiving invasive mechanical ventilation or oxygen, is a corticosteroid that has anti-inflammatory and immunosuppressive properties. Biological medicines, in turn, such as monoclonal antibodies, interferons, specific proteins and anticoagulants are being evaluated in various clinical trials to define their role in disease therapy. The World Health Organization (WHO) warned that the coronavirus may never disappear, even with a possible vaccine, highlighting the urgency of research into new innovative drugs. The most realistic current scenario involves the development of specific antivirals against Sars-CoV-2 for the safe and effective treatment of the disease.